Intellectual Capital (IC) Analysis and The Effect to Financial Performance in PT Kalasuba Indonesia (KSI) - Dwi Ermayanti Susilo; Amirotul Roifah; Samsul Hadi (Binus Business Review, 2016)
Financial Performance (FP) is one of the important things for a company to know the development of the company. One important thing that influences FP is the Intellectual Capital (IC). Research was conducted to get the best IC analysis in order to get success and fulfill the daily human needs which always increases. Therefore, it had research problem ‘how was the components of IC affecting the FP of PT Kalasuba Indonesia (KSI), and the objective is to explore the IC components in affecting the FP. It was interesting to be explored because it had unique characteristics, which consist of spiritual knowledge, attitude, discipline, management knowledge and managerial experience, as well as skill and capabilities, in which the first three points were different from the rest. It used qualitative analysis method as the instrument. It was done by collecting the data through observation and was analyzed using the Robbins theory. It can be concluded that those five IC has important effect in increasing FP of PT KSI and keeping it stable.